Contrasting patterns of persistence and diversification in vicars of a widespread Australian lizard lineage (the Oedura marmorata complex). (19th July 2014) - Oliver, Paul M.; Smith, Katie L.; Laver, Rebecca J.; Doughty, Paul; Adams, Mark; Riddle, Brett
Abstract Aim Lineages in many parts of the world have distributions that have been shaped by range contraction in the face of deteriorating climatic conditions through the Neogene. When such lineages now consist of widely spaced vicariant populations (vicars) they provide opportunities (1) to compare and contrast the timing and pattern of diversification within and between major geographical regions, and (2) to examine how differential interactions with geography, climate and localized adaptation may have shaped idiosyncratic patterns of genetic diversification. Location Australian Arid Zone (AAZ) and Australian Monsoonal Tropics (AMT). Methods We compiled and analysed mitochondrial DNA, nuclear DNA and allozyme datasets to determine the evolutionary history and genetic diversity of isolated populations of a gecko lineage (the Oedura marmorata complex and related taxa) distributed across the Australian monsoonal and arid biomes. Results Three widely allopatric lineages in the AAZ diverged during the late Miocene and Plio‐Pleistocene. Populations in the AMT display much greater genetic turnover than those in the AAZ over equivalent geographical distances, and also include several lineages that are of equal or greater age than all diversity in the AAZ. Saxicoline lineages tend to show higher genetic diversity and/or have more restricted ranges than arboreal relatives in both biomes. Main conclusions Lineages of Oedura show contrasting patterns of diversification in the two major biomes they inhabit. Diversity in the arid biome is younger and restricted to widely separated refugia, reflecting the younger age and pervasive harshness of this environment. Higher diversity in the AMT is also indicative of persistence, but at much finer geographical scales and broadly over a longer period of time, perhaps reflecting the more continuous spatial and temporal distribution of equitable habitats within this region. Finally, the wider distribution of arboreal lineages in both biomes suggests that ecological flexibility has also shaped the contrasting patterns of distribution in related lineages, and supports the contention that an association with rocks has shaped high lineage diversity in many taxa from the Australian Monsoonal Tropics.